2018
DOI: 10.18632/oncotarget.24701
|View full text |Cite
|
Sign up to set email alerts
|

Indolent lymphoma with composite histology and simultaneous transformation at initial diagnosis exhibit clinical features similar to de novo diffuse large B-cell lymphoma

Abstract: While various studies characterized clinical and prognostic properties of de novo diffuse large B-Cell lymphoma (DLBCL) and transformed indolent lymphomas, the clinicopathological features of indolent lymphoma and simultaneous secondary transformation upon initial diagnosis (ssDLBCL) are insufficiently established.Between 2010 and 2017, 247 consecutive patients admitted to our institution and treated for DLBCL were investigated for composite histology of ssDLBCL-type. Upon systematical histopathological evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…Our study also suggests that patients with composite FL and DLBCL carrying the ABC subtype tended to have a shorter OS as compared to those with the GCB subtype, even though this finding was short of statistical significance and not incorporated into the CGI model. This is similar to the findings reported in Witte et al, 2018 where non-germinal centre derived composite FL and DLBCL had an inferior clinical outcome bordering on statistical significance as compared to cases with GCB subtype 26 . We compared these results to studies analysing the prognostic value of Han's algorithm in de novo DLBCL.…”
Section: Discussionsupporting
confidence: 90%
“…Our study also suggests that patients with composite FL and DLBCL carrying the ABC subtype tended to have a shorter OS as compared to those with the GCB subtype, even though this finding was short of statistical significance and not incorporated into the CGI model. This is similar to the findings reported in Witte et al, 2018 where non-germinal centre derived composite FL and DLBCL had an inferior clinical outcome bordering on statistical significance as compared to cases with GCB subtype 26 . We compared these results to studies analysing the prognostic value of Han's algorithm in de novo DLBCL.…”
Section: Discussionsupporting
confidence: 90%
“…This distribution pattern of COO is consistent with results from prior smaller studies. 9,10 In contrast, for DLBCL concurrent with other indolent NHLs, the GCB and the non-GCB subtypes were equally common in our series (thus enriched for non-GCB relative to DLBCL alone cases). One recent study reported that DLBCL with discordant bone marrow involvement was predominantly the GCB subtype, 14 although some cases may have had FL in the bone marrow.…”
Section: Discussionmentioning
confidence: 53%
“…[4][5][6] In the rituximab era, several small retrospective series of concurrent DLBCL and FL (,60 cases each) have been described, with contradicting results for PFS and OS in comparison with DLBCL. [7][8][9][10] Likewise, DLBCL with discordant bone marrow involvement of an indolent NHL has been retrospectively studied by several groups, [11][12][13][14] most of which included ,60 cases except for a recent MD Anderson study (n 5 90), 14 again with inconsistent results regarding PFS compared with DLBCL without bone marrow involvement.…”
Section: Introductionmentioning
confidence: 99%
“…21 Conversely, another study revealed that concurrent DLBCL with indolent lymphoma other than follicular lymphoma has a significantly poor prognosis. 22 Indeed, one MZL case in the mediastinum that transformed to DLBCL was refractory to R-CHOP therapy. 23 Therefore, although CMR with chemoradiotherapy was achieved in our case, careful follow-up is necessary in the future.…”
Section: Discussionmentioning
confidence: 99%